VD_FINDINFO HC / 2012 / 354 vom 29. Mai 2012 - VD Tribunal cantonal (2012)
RÉSILIATION, BAIL À LOYER, COLOCATAIRE, CONSORITÉ, ACTION EN CONTESTATION | 273 al. 1 CO, 210 CPC (CH), 211 al. 2 CPC (CH), 319 let. b ch. 2 CPC (CH)